A influência da responsabilidade social percebida na marca e na satisfação mediadas pela motivação do consumo: um estudo sobre aplicativos de entrega de comida - Fonseca, Márcio Ribeiro da (2022)
This study aims to evaluate the influence of Corporate Social Responsibility Perceived by the consumer on the Brand Equity and Satisfaction with the mediation of the Motivations of Convenience and Hedonics of the user of the Food Delivery Mobile Applications.The concept of Corporate Social Responsibility has been widely studied, however, there is no consensus among researchers about the measurement of the construct and the proposal of a unified scale. This thesis innovates by presenting a new perspective on the measurement of Perceived CSR by proposing a scale adapted for Brazil, starting from the CSRConsPersScale, developed from Tripe Botton Line for a sector that has grown a lot in recent years and was driven by the Covid-19 pandemic, which is Food Delivery Mobile Apps. The adaptation and translation of the scale items that make up the questionnaire were carried out through interviews with experts, followed by two surveys, for which Exploratory Factor Analysis (n=222) and Confirmatory Factor Analysis with the use of Structural Equation Modeling (n=408) were conducted. Sociodemographic data were used as control variables and 38 hypotheses were tested, of which 27 were confirmed. The results show that, in the researched sample, there was a positive and significant influence of the Perceived CSR in all the dependent variables tested. The results show that, in the researched sample, there was a positive and significant influence of the Perceived CSR on all the dependent variables tested, confirming that the company's social responsibility initiatives contribute to the construction of strong brand associations and positively impact satisfaction, increasing the likelihood of recommendations. The results also indicated that Perceived CSR is mediated by the Convenience and Hedonic Motivation of users of mobile food delivery applications with a few exceptions, however, not all sociodemographic data showed significant results when used as control variables. Based on the results achieved, the proposed conceptual model was validated and adjusted, and the applicability of this study is evidenced by indicating theoretical contributions, managerial practices and recommendations for future studies in a sector that is still little studied in Brazil.